2000
DOI: 10.1046/j.1365-2648.2000.01478.x
|View full text |Cite
|
Sign up to set email alerts
|

Determining chest pain patients’ suitability for transfer to a general ward following admission to a cardiac care unit

Abstract: The objective of this study was to assess the performance of a consensus-derived decision algorithm in determining chest pain patients' suitability for early transfer to a lower dependency ward by predicting complications. The sample comprised 516 patients with chest pain presumed to be cardiac in origin, admitted to a cardiac care unit (CCU) in northern England from the community or from the accident and emergency department. A decision algorithm was designed following a review of the literature and amended t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…The major source of discordance or misclassification was that nurses tended to overestimate disease severity in this study. However, this is the opposite of findings from a study by Quinn et al [60]. In their study CCU nurses were more likely to identify a chest pain patient as suitable for admission to a general ward, compared with a physician-derived algorithm.…”
Section: Triagementioning
confidence: 46%
“…The major source of discordance or misclassification was that nurses tended to overestimate disease severity in this study. However, this is the opposite of findings from a study by Quinn et al [60]. In their study CCU nurses were more likely to identify a chest pain patient as suitable for admission to a general ward, compared with a physician-derived algorithm.…”
Section: Triagementioning
confidence: 46%
“…In addition a study by Quinn et al [18] also found that coronary care nurses in a hospital in the North of England were skilled in the assessment of their patient's cardiac conditions and were able to distinguish between those that require differing levels of nursing care. This single centre study was developed to investigate the performance of an algorithm that may be used to identify patients suitable for early transfer from the coronary care unit.…”
Section: Patient Assessment and Managementmentioning
confidence: 95%
“…Three studies have examined the appropriateness of nurse triage decision‐making (Leprohon & Patel 1995, Considine et al. 2000, Quinn et al. 2000).…”
Section: Evaluating Decisions In Nursing Practicementioning
confidence: 99%
“…As in the research into judgement, the study by Quinn et al. (2000) has a strength in that it compares nurses’ decisions to actual patient outcomes.…”
Section: Evaluating Decisions In Nursing Practicementioning
confidence: 99%
See 1 more Smart Citation